Anterior hip dislocation in young patient obturator (inferior) type: a rare case report - Kulambi, Vijaykumar; Chaudhari, Kartavya; Pethapara, Vickykumar (International Journal of Research in Orthopaedics, 2018)
Obturator type traumatic anterior hip dislocation in adult is rare of all type of hip dislocation. Here we described a case with same description. A patient 30 years male residing at Hoovina Hadagali, Bellary district, Karnataka met road traffic accident of his car while he was sitting in front seat with thigh abducted. He was brought to emergency room where he was diagnosed as obturator type of anterior right hip dislocation and closed reduction was achieved within 2 hours. Patient was posted for closed reduction of right hip under general anaesthesia which achieved by Alli’s maneuver followed by traction and immobilisation with Thomas splint. 3 weeks of immobilisation followed by progressive mobilisation and loading patient was able to walk without any complaint with normal range of movements after 6 months.